The Phenomenon of Fanaticism in the Cosplay Lampung Fun Community (Phenomenological Study of Fanaticism in the Japanese Cartoon Jujutsu Kaisen) - Fitriandini, Ragil; M. Denu Poyo; Noning Verawati; Hanindyalaila Pienrasmi; Budhi Waskito; Wawan Hernawan (International Journal of Education, Vocational and Social Science, 2024)
This research discusses the Phenomenon of Fanaticism in the Japanese Cartoon Jujutsu Kaisen (Phenomenological Study in the Cosplay Lampung Fun Community in Bandar Lampung). The problem raised here is why members of the Cosplay Lampung Fun Community are fanatical about the Japanese cartoon Jujutsu Kaisen and how the fanaticism process occurs. This research was conducted to find out more about why the Cosplay Lampung Fun community is fanatical about Japanese cartoons and to explain the process by which this fanaticism occurred. This research was conducted using a qualitative approach method. By using this approach, we are able to explain and describe the phenomenon of fanaticism that occurs among members of the Cosplay Lampung Fun community. This research was conducted from November 2023 to February 2024. Data collection was carried out by environmental observation and interviews with informants who met the requirements for this research. The results obtained from this research are the reasons and the breakdown of fanaticism that occurs among members of the Cosplay Lampung Fun community, through cause motives and goal motives can influence the way they dressed by doing cosplay, from the food they eat because it is inspired by a scene in the anime to they lifestyle like going to the gym because they want to look like one of the characters in Jujutsu Kaisen.